Cross‐Cultural Adaptation of the Clinical Frailty Scale for Critically Ill Patients in Spain and Concurrent Validity With FRAIL‐Es - Susana Arias‐Rivera; María Nieves Moro‐Tejedor; Fernando Frutos‐Vivar; Cristina Andreu‐Vázquez; Israel John Thuissard‐Vasallo; María Mar Sánchez‐Sánchez; Raquel Sánchez‐Izquierdo; Lorena Oteiza‐López; Sonia López‐Cuenca; Marta Checa‐López; Raquel Jareño‐Collado; Virginia López‐López; et al. (Nursing Open)
ABSTRACT Aims To adapt the Clinical Frailty Scale (CFS) into Spanish and assess its concordance with the Spanish version of the FRAIL scale (FRAIL‐Es) in the context of intensive care. Design Validation study of frailty assessment scales in critically ill patients. Methods The study was conducted in two phases. The first phase consisted of translating, culturally adapting, and validating the CFS into Spanish. The second phase consisted of a metric descriptive study to assess the concurrent criterion validity of the adapted CFS with FRAIL‐Es in a cohort of intensive care patients. Both scales were assessed upon admission to intensive care and at 3, 6, 9, and 12 months post‐hospital discharge. Analysis was performed using T‐Student/Mann–Whitney, chi‐squared and Cohen's Kappa tests. Results Successful adaptation of the CFS with minimal changes was achieved, demonstrating its applicability in the evaluated context. The pilot study indicated that CFS‐Es is easy to assess, but some subjectivity in interpretation was noted. CFS‐Es and FRAIL‐Es were applied to 212 patients, revealing variations in frailty prevalence. The concordance and correlation between the CFS and FRAIL scales are robust. These differences suggest that the choice of scale may impact the identification of frail patients. These results emphasise the importance of considering specific characteristics of each scale when assessing frailty in critically ill patients, providing valuable information for clinical implementation and research in this field. Patient or Public Contribution Assessing frailty upon admission can be helpful in the care of frail patients, allowing the development of specific care plans based on pre‐existing frailty.